Point Load Strength of Calcitic Marble from the Kuala Lumpur Limestone, Peninsular Malaysia - J.K, Raj (Malaysian Journal of Science, 2006)
Diametral tests on fine grained calcitic marble cores from the Kuala Lumpur Limestone, with loading parallel, and perpendicular, to an inherent colour banding, yield point load indices [Isâ‚â‚…â‚€â‚Ž] of 3.14 MPa, and 3.93 MPa, respectively, whilst similar tests on medium grained cores yield indices of 3.41 MPa, and 4.44 MPa. Diametral tests on coarse grained marble cores, with loading parallel and perpendicular to the inherent banding yield indices [Isâ‚â‚…â‚€â‚Ž] of 3.57 MPa, and 5.03 MPa, respectively. These variations in point load strength are considered to result from differences in the preferential alignment and number of inter-granular borders; the coarse grained marble with relatively fewer borders showing the highest strength. It is concluded that the point load test allows for an effective strength classification of the calcitic marble, though the results need evaluation with reference to inherent textural features.